Graphene Synthesis and Processing on Ge Substrates. (29th March 2017) - Lupina, G.; Lukosius, M.; Lippert, G.; Dabrowski, J.; Kitzmann, J.; Lisker, M.; Kulse, P.; Krüger, A.; Fursenko, O.; Costina, I.; Trusch, A.; Yamamoto, Y.; et al.
Abstract : We review some of the recent results obtained on the graphene synthesis on Ge(100)/Si(100) substrates by molecular beam epitaxy and wafer scale chemical vapor deposition. We outline some of the identified challenges in synthesis and present first experimental results on patterning and in-line metrology of graphene in a 200 mm wafer pilot line.